Birthing Ball Gymnastics Technique to Reduce Labor Morbidity and Mortality - Fijri Rachmawati (Placentum, 2025)
Background: For a woman, discomfort, fear and pain are problems during labor. Pain during the first stage of labor is intense and prolonged, thus necessitating proper management to address it. Labor pain and its management are critical concerns for women. The pain arises from both physical reflexes and the psychological response of the mother, including anxiety and fear, which can lead to panic. Effective pain management can provide an unforgettable experience. Addressing labor pain is a crucial intervention, and the birthing ball has proven to be an important tool in this regard. Birthing ball is a non-pharmacological method to reduce labor pain, the mother can have a positive birth experience, as it increases cervical dilatation and also expands the pelvic cavity, helping to align the longitudinal axis of the fetus with the birth axis which in turn shortens the duration of the first stage and supports vaginal delivery, the upright position during labor encourages the descent of the fetus aided by gravity, while also increasing pelvic dimensions. Women who use the birthing ball also feel psychologically empowered as they take an active role in their own care during labor, aiding in pain management.